Commentary: Addiction, Stigma, and Neurodiversity - Sussman, Steve (Evaluation & the health professions, 2021)
The addictions are subject to a great deal of stigma, the constituents of which include negative attributions such as being immoral, weak-willed, or sick. Negative outcomes include exclusion from positive life opportunities. In this commentary, I briefly discuss the definition of stigma, descriptors of addiction-related stigma, and negative consequences. Solutions to reduce addiction-related stigma are mentioned including providing greater interpersonal exposure to persons recovering from addiction, corrective information education, altering the language used to describe and classify persons who have suffered from addiction, and possibly viewing addiction vulnerability as an example of neurodiversity, as opposed to a character flaw or a disease. Suggestions for future research on reducing addiction-related stigma are suggested.